Transaksi Perbankan Syariah Dalam Perspektif UU No. 21 Tahun 2008 Dan Hadits Muslim - Bimo Satrio Wicaksono; Tajul Arifin (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Sharia banking is a financial institution that has a very important role in advancing the Indonesian economy and is an answer to the public's need to use a banking system based on sharia principles. However, sometimes there are many perceptions that Islamic banking is the same as conventional banking. Sharia banking has fundamental differences from conventional banking, namely regarding legal aspects, organizational structure, financed business activities and work environment. Sharia banking operational activities are based on sharia principles, namely the principle of profit sharing, buying and selling and leasing principles by conducting business through mudharabah, musyarokah, murabbahah and ijaroh contracts. Meanwhile, conventional banking provides services in payment traffic with the principle of determining interest for both savings and loan (credit) products and applying various fees in the form of nominal amounts and certain percentages.